O021 Investigation of a novel LED lighting strategy designed to accelerate circadian entrainment to night shift-work in an encapsulated environment. (9th November 2022) - Guyett, A; Scott, H; Lechat, B; Manners, J; Stuart, N; Lack, L; Kemps, E; Eckert, D; Micic, G; Banks, S; Dorrian, J; Adams, R; et al.
Abstract: Introduction: Shift-work results in misalignment between circadian timing and the sleep/wake schedule, negatively impacting sleep and performance. In encapsulated environments (e.g., submarines), the lack of strong daily lighting cues impairs circadian entrainment. This study tested whether circadian-informed LED lighting promotes greater circadian phase delays to adjust to night shift-work compared to standard lighting. Method: To date, 11 healthy sleepers (7 males, mean±SD age27.6±8.5 y, N=24 anticipated) have completed two separate 8-day experimental conditions (circadian-informed lighting versus standard lighting). After a baseline sleep from 22:00 – 07:00 (day 1) and salivary dim light melatonin onset ([DLMO], day 2), participants undertook simulated night shift-work (00:00 - 08:00) and slept during the daytime (10:00 - 19:00) for days 3-7 followed by a post-DLMO assessment on day 8. Ingestible capsules collected core body temperature (CBT) continuously throughout days 2-8. The standard lighting condition mimicked current lighting on submarines (largely dim, blue-depleted light), while the circadian-informed lighting administered bright, blue-enriched and dim, blue-depleted lighting at times estimated to facilitate rapid circadian delay. Cosine curve fitting was applied to the CBT data to estimate temperature minima (CBTmin) and determine phase delay magnitude for comparison across conditions. Results: There was a significant day-by-condition interaction on CBTmin (F4, 88=2.82, p=0.030). By day 6, the CBTmin delay was (mean±SD) 3.2±.97 hours greater in the circadian-informed lighting versus standard lighting, p=0.001. Conclusions: These preliminary analyses support that circadian-informed lighting accelerates circadian re-adjustment to night shift-work. Such interventions could improve sleep, performance, and safety in shift-workers who work in encapsulated environments.